Towards a description of the functions of cognitive and non-cognitive meaning in the communicative competence of second language learners - Alano, Angeles Calsado 1924- (1979)
This study was undertaken to determine the communicative competence of second language learners of English who are fourth year high school, second year college, and graduate students on the master's level in terms of their command of the cognitive meaning. Full command of cognitive and non-cognitive meaning was evaluated by administering the research instrument composed of four measures in mimeographed form which respondents were required to answer in written form. In comparison of the results between the boys and the girls, the girls achieved better command of the cognitive and non-cognitive meaning.
Mimeographed.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Vita.
Keywords: English language -- Study and teaching -- Foreign speakers; Communicative competence